The Relationship Between Islam and Traditional Marriage of Siak Malay - Zikri Darussamin; Rahman Rahman; Imam Ghozali (Justicia Islamica, 2020)
This research focuses on the marriage customs of the Siak Malay Society. The research focuses are three stages of the tradition: they are the stage before, during, and after the wedding ceremony. The traditional wedding procession needs to find common ground between Islamic Law and custom living in the Siak Malay Society. This research uses a qualitative descriptive-analytic approach. The collecting data method combines the library and field research through interviews with related parties. The results of every stage, before, during, and after the wedding ceremony, firstly, shows that it has religious, philosophical meanings come from the teachings of Islam, i.e., Qur’an, Hadith, and Ijtihad using the ”˜urf frame of mind. The rule explains that whatever has been determined by the syara’, absolutely without any definite provisions in religion and language, is returned to ”˜urf. Second, the relationship between Islamic Law and custom in this wedding tradition in the historical context originated from the traditions carried out by the Siak Sri Indrapura Kingdom. This is due to the Sultan’s function as the Head of State and the spiritual guide at that time, including marriage matters. This has implications for the mixing of the wedding procession traditions containing religious values packaged in cultural forms; thus, that the wedding tradition of the Siak Malay society needs to be maintained and preserved as a part of the cultural wealth with Islamic nuances without burdening the economies of both parties in the implementation of the wedding ceremony procession.Penelitian ini memfokuskan pada adat perkawinan Masyarakat Melayu Siak. Ada tiga tahapan tradisi yang menjadi fokus penelitian, yaitu tahap sebelum pesta perkawinan, tahap sedang berlangsung pesta perkawinan, dan tahap setelah pesta perkawinan.  Prosesi adat perkawinan tersebut perlu dicari titik temu antara hukum Islam dan adat yang telah hidup di Masyarakat Melayu Siak. Penelitian ini menggunakan pendekatan kualitataif deskriptif analitis. Sedangkan metode pengumpulan data dalam penelitian ini menggabungkan antara Metode kepustakaan dan penelitian lapangan dengan melakukan wawancara terhadap pihak-pihak yang terkait. Hasil penelitian menunjukan bahwa: Pertama, pada setiap rangkaian tradisi pesta perkawinan mulai dari sebelum pesta perkawinan, sedang pesta perkawinan dan setelah pesta perkawinan ternyata mempunyai makna-makna filosofis keagamaan yang bersumber dari ajaran agama Islam baik Al-Qur’an, Hadist, dan Ijtihad menggunakan kerangka berfikir ”˜urf. Kaidah ini menjelaskan bahwa setiap apapun yang telah ditetapkan oleh syara` secara mutlak tanpa ada ketentuannya secara pasti dalam agama dan dalam bahasa, maka hal tersebut dikembalikan kepada ”˜urf. Kedua, hubungan hukum Islam dan adat pada tradisi perkawinan ini dalam konteks sejarah berawal dari tradisi yang dilakukan oleh Kerajaan Siak Sri Indrapura. Hal ini karena fungsi Sultan sebagai Kepala Negara sekaligus sebagai pembimbing agama waktu itu, termasuk juga dalam hal perkawinan. Ini berimplikasi pada percampuran tradisi prosesi perkawinan mengandung nilai-nilai agama yang dikemas dalam wujud budaya. Sehingga tradisi perkawinan masyarakat Melayu Siak perlu dipertahankan dan dilestarikan sebagai bagian kekayaan budaya yang bernuansa Islami dengan tidak memberatkan ekonomi kedua belah pihak dalam pelaksanaan prosesi perkawinan.